Super-high-resolution aerial imagery, digital surface model and 3D point cloud of Cape Simpson, Alaska (subset 05) - Tabea Rettelbach; Ingmar Nitze; Inge Grünberg; Jennika Hammar; Simon Schäffler; Daniel Hein; Matthias Gessner; Tilman Bucher; Jörg Brauchle; Jörg Hartmann; Torsten Sachs; Julia Boike; et al. (PANGAEA, 2024)
As part of the ThawTrend-Air airborne campaign led by the Alfred Wegener Institute in 2019, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at a spatial resolution of 7 cm, as well as photogrammetric point clouds in RGB and NIR at 24.98 pts/m^2 and 9.42 pts/m^2, respectively. This dataset covers approximately 4,83 km^2 of Cape Simpson in Alaska, with all images collected on 19 July 2019. This super-high-resolution dataset provides opportunities for generating detailed training datasets of permafrost landform inventories, a baseline for change detection for thermokarst and thermo-erosion processes, and upscaling of field measurements to lower-resolution satellite observations.
In: Rettelbach, T et al. (2024): Super-high-resolution aerial imagery, digital surface models and 3D point clouds of Cape Simpson, Alaska [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.962039